Implementasi Metode Demonstrasi Pada Mata Pelajaran PAI - Iis Khomisah; Syafe’i.R; Fathurrohman.A (TANZHIMUNA : Jurnal Manajemen Pendidikan Islam, 2021)
Implementation of Demonstration Methods in PAI Subjects on Body Care Sub Material SMK Negeri 1 Cipanas. This research is motivated by the large number of families who cannotafford the care of the corpse so it is carried out by other people. The purpose of this study was to determine the planning, implementation, and evaluation of demonstration methods of PAI subjects in the sub-material of corpse care at SMK Negeri 1 Cipanas , Cianjur Regency and it is hoped that it can provide useful contributions for the future of students. The method used by researchers is descriptive with a qualitative approach. Data collection techniques through observation, interviews, and documentation. The results of this study indicate that the planning of learning PAI K-13 material for body care in class XI SMK Negeri 1 Cipanas Cianjur has been prepared by the government where the PAI teacher only implements it. The implementation of PAI learning material for body care uses a scientific approach with a demonstration method. Evaluation of PAI learning material on body care in class XI SMK Negeri 1 Cipanas Cianjur includes three aspects, including affective, psychomotor, and cognitive assessment. The supporting factors for the implementation of the demonstration method in PAI learning material on the care of the corpse at SMK Negeri 1 Cipanas include: teachers, students, learning environment and facilities. Meanwhile, the inhibiting factor is the lack of critical attitude of students in learning PAI in the material of funeral care.